A Functional Alternative Oxidase Modulates Plant Salt Tolerance in Physcomitrella patens. (23rd May 2019) - Wu, Guochun; Li, Sha; Li, Xiaochuan; Liu, Yunhong; Zhao, Shuangshuang; Liu, Baohui; Zhou, Huapeng; Lin, Honghui
Abstract: Alternative oxidase (AOX) has been reported to be involved in mitochondrial function and redox homeostasis, thus playing an essential role in plant growth as well as stress responses. However, its biological functions in nonseed plants have not been well characterized. Here, we report that AOX participates in plant salt tolerance regulation in moss Physcomitrella patens ( P. patens ). AOX is highly conserved and localizes to mitochondria in P. patens . We observed that PpAOX rescued the impaired cyanide (CN)-resistant alternative (Alt) respiratory pathway in Arabidopsis thaliana (Arabidopsis) aox1a mutant. PpAOX transcription and Alt respiration were induced upon salt stress in P. patens . Using homologous recombination, we generated PpAOX -overexpressing lines ( PpAOX OX). PpAOX OX plants exhibited higher Alt respiration and lower total reactive oxygen species accumulation under salt stress condition. Strikingly, we observed that PpAOX OX plants displayed decreased salt tolerance. Overexpression of PpAOX disturbed redox homeostasis in chloroplasts. Meanwhile, chloroplast structure was adversely affected in PpAOX OX plants in contrast to wild-type (WT) P. patens . We found that photosynthetic activity in PpAOX OX plants was also lower compared with that in WT. Together, our work revealed that AOX participates in plant salt tolerance in P. patens and there is a functional link between mitochondria and chloroplast under challenging conditions.